2015
DOI: 10.1007/s00787-015-0729-x
|View full text |Cite
|
Sign up to set email alerts
|

New evidence of factor structure and measurement invariance of the SDQ across five European nations

Abstract: International audienceThe main purpose of the present study was to analyse the internal structure and to test the measurement invariance of the Strengths and Difficulties Questionnaire (SDQ), self-reported version, in five European countries. The sample consisted of 3012 adolescents aged between 12 and 17 years (M = 14.20; SD = 0.83). The five-factor model (with correlated errors added), and the five-factor model (with correlated errors added) with the reverse-worded items allowed to cross-load on the Prosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 55 publications
(129 reference statements)
11
75
3
1
Order By: Relevance
“…The CFA model may be varied to allow identification of partial measurement invariance by imposing equality constraints on item thresholds, factor loadings or error variances across groups. Significant differences between the constrained and unconstrained models indicate full invariance is not supported (Milfont & Fischer, ; Ortuño‐Sierra et al, ). Finally, scalar invariance – justifying mean score comparisons – is tested by constraining item intercepts to be equal across groups (Milfont & Fischer, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CFA model may be varied to allow identification of partial measurement invariance by imposing equality constraints on item thresholds, factor loadings or error variances across groups. Significant differences between the constrained and unconstrained models indicate full invariance is not supported (Milfont & Fischer, ; Ortuño‐Sierra et al, ). Finally, scalar invariance – justifying mean score comparisons – is tested by constraining item intercepts to be equal across groups (Milfont & Fischer, ).…”
Section: Resultsmentioning
confidence: 99%
“…Other inter‐country comparisons of the S‐SDQ, such as made by Stevanovic et al (), also found poor fit for a 5‐factor model, with a 3‐factor model providing a better but non‐invariant fit across five European countries (Germany, Cyprus, England, Sweden, Italy; Essau et al, ), and partial measurement invariance with DIF for 11 items across Spain, England, Ireland, Germany and France (Ortuño‐Sierra et al, ). Ortuño‐Sierra et al () suggested that greater cultural differences may explain greater disparities in factor structure found by Stevanovic et al (), who compared Turkey, Serbia, Bulgaria, Croatia, Inda, Indonesia, and Nigeria.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There appear to be some cultural differences in behaviour, or in how preschool teachers already estimate behaviour at preschool age. According to work conducted by Ortuño-Sierra et al (2015), various modifications of the present SDQ scales could be required if emotional and behavioural problems are to be screened in different European countries. It is difficult to comment upon differences around the world in general as the SDQ has been mostly studied and used in Europe and Australia (Borg et al, 2012;Warnick, Bracken & Kasl, 2008).…”
Section: Preschool Teachers Can Identify Behavioural Problems Among Pmentioning
confidence: 99%